2019
DOI: 10.1093/jnci/djz011
|View full text |Cite
|
Sign up to set email alerts
|

The National Cancer Institute Clinical Trials Planning Meeting for Prevention and Treatment of Chemotherapy-Induced Peripheral Neuropathy

Abstract: Although recent scientific advances have improved our understanding of basic biological mechanisms underlying chemotherapy-induced peripheral neuropathy (CIPN), few interventions are available to prevent or treat CIPN. Although some biological targets from preclinical studies show promise in nonhuman animal models, few targets have been translated to successful clinical trials. To address this problem, the National Cancer Institute’s Symptom Management and Health-Related Quality of Life Steering Committee conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 39 publications
1
65
0
1
Order By: Relevance
“…Overall CIPN incidence was lower in this study than that reported in the literature, and this has to do probably with the scales used; past studies have used quality of life scales to estimate CIPN, which often include a range of general/broader items to indicate neuropathy. Also, clinician‐based assessments, such as the NCI‐CTCAE tend to underestimate CIPN incidence (Dorsey et al, ). We have explained these reasons in more detail in the parent larger study (Molassiotis et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall CIPN incidence was lower in this study than that reported in the literature, and this has to do probably with the scales used; past studies have used quality of life scales to estimate CIPN, which often include a range of general/broader items to indicate neuropathy. Also, clinician‐based assessments, such as the NCI‐CTCAE tend to underestimate CIPN incidence (Dorsey et al, ). We have explained these reasons in more detail in the parent larger study (Molassiotis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect sensitivity or reliability issues with the various scales measuring CIPN. As the measurement tool(s) used in future risk factor research will be related with the identification of specific risk factors, it is important to use the most reliable and valid CIPN scale (Cavaletti et al, ; Dorsey et al, ) or a combination of scales to maximize the “pick up” rates of these tools that will include both patient‐reported outcomes and objective CIPN indicators, such as with the Total Neuropathy Score clinical version (TNSc) (McCrary et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several recommendations have recently been published concerning the assessment of CIPN in the clinical trial setting . These have highlighted the unsuitability of the NCI‐CTCAE as a trial endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread use of these medications, to date duloxetine, a serotonin‐norepinephrine reuptake inhibitor has been the only drug found to be associated with a significant reduction in neuropathic pain in CIPN in a randomized phase III intervention study (Table ) . The mechanism of duloxetine‐induced analgesia is due to the blocking of serotonin and norepinephrine transporters, as well as blocking of sodium channel currents and affecting the descending inhibitory pain neural networks Additional novel therapeutic strategies are currently in development …”
Section: Treatment Of Established Pipn: Clinical Trial Strategiesmentioning
confidence: 99%